THE HISTORY OF BUKHARA EMIRATE IN THE RESEARCHES OF ENGLISH-SPEAKING AUTHORS - Muhammadali, Mubinov (Journal of Learning on History and Social Sciences, 2025)
Objective: This paper systematizes and analyzes historiographic materials by English-speaking authors on Bukhara Emirate’s history, identifying research trends, changes, and results while offering insights for the future development of historiography on this topic. Method: The study applies comparative, analytical, and historiographic methods, synthesizing primary and secondary sources, critically assessing colonial and Orientalist perspectives, and categorizing research into political, economic, and socio-cultural dimensions. Results: The paper reveals evolving Western perspectives on Bukhara Emirate, distinguishing colonial biases from objective insights, highlighting key contributions by 19th-20th-century scholars, and outlining historiographic gaps requiring further interdisciplinary research. Novelty: It provides a systematic historiographic assessment of English-language research on Bukhara Emirate, critically examining ideological influences and academic trends while proposing new directions for future studies in Central Asian historiography.